ВДОСКОНАЛЕННЯ ВИМІРЮВАЛЬНОГО КОНТРОЛЮ ІМПУЛЬСНИХ СПОТВОРЕНЬ НАПРУГИ МЕРЕЖІ - Сівей, Вей; Ванько, В.М.; Кочан, О.В.; Кочан, Р.В.; Цзюнь , Су (Інститут електродинаміки НАН України, Київ, 2019)
The method for detecting and tracking pulse distortion of voltage in the power network is proposed. Its idea is the comparison of the rates of change of voltage between the power network and the sinusoidal signal. The structure of the measurement instrument for measuring the dynamic parameters of electricity is developed in this paper. References 16, figures 2, table 1.